2016
DOI: 10.2519/jospt.2016.6493
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Electromyographic Activity of the Superior and Inferior Portions of the Gluteus Maximus Muscle During Common Therapeutic Exercises

Abstract: T T CONCLUSION:The results of the present study demonstrate preferential activation of the superior portion of the gluteus maximus during exercises that incorporate elements of hip abduction and/ or external rotation. In contrast, exercises that primarily involve hip extension target both portions of the gluteus maximus to a similar extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 29 publications
4
26
0
Order By: Relevance
“…The UGM is located in the superficial layer [15], and because of its anatomical structure, its primary role is abduction of the hip joint as well as extension and external rotation [42]. Our findings are in agreement with those of Selkowitz et al [51] who reported that the superior gluteus maximus EMG activity is greater than the incorporated hip abduction and/or external rotation movements. Thus, the results of the T2 values in the UGM showed that side-lying hip abduction with external rotation and extension activated compared with the sidelying hip abduction with neutral hip or internal rotation and flexion.…”
Section: Discussionsupporting
confidence: 93%
“…The UGM is located in the superficial layer [15], and because of its anatomical structure, its primary role is abduction of the hip joint as well as extension and external rotation [42]. Our findings are in agreement with those of Selkowitz et al [51] who reported that the superior gluteus maximus EMG activity is greater than the incorporated hip abduction and/or external rotation movements. Thus, the results of the T2 values in the UGM showed that side-lying hip abduction with external rotation and extension activated compared with the sidelying hip abduction with neutral hip or internal rotation and flexion.…”
Section: Discussionsupporting
confidence: 93%
“…UGMax was preferentially recruited in Clam and HABD while UGMax and LGMax were equally activated in the isometric and eccentric phases of PHE. Our findings concur the recruitment pattern of GMax reported by Selkowitz et al [8] and Lyons et al [28] in which the UGMax is predominantly functioning as the hip abductor and external rotator, whereas the LGMax mainly acts as a hip extensor. With reference to the fiber orientation of the UGMax in which it inserts into the fascia latae and hence it facilitates hip abduction, while LGMax contains a larger moment arm for hip extension [29].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the effect of abdominal core activation was only examined during the isometric phase of exercises. In studies conducted by Chance-Larsen et al [4] and Oh et al [5], the activity of gluteus maximus (GMax) was assessed as a single unit in which the functional differences of the subdivisions of GMax were not considered [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Starkly contrasting to the BFlh, the gluteus maximus possesses robust architecture with its large area of attachment at the pelvic region producing a broad, square muscle, segmented into at least two subdivisions (Barker et al, 2014). A superior portion converges to the iliotibial band and is seen to elicit hip extension, abduction and lateral rotation (Selkowitz et al, 2016;Pirouzi et al, 2006). An inferior portion inserts directly on to the femur at the gluteal tuberosity (Kendall et al, 2005;Winter 2005) and is primarily a hip extensor but may assist lateral rotation (McAndrew et al, 2006) in addition to adduction (Floyd, 2009).…”
Section: Gluteal and Adductor Synergists: Joined At The Hipmentioning
confidence: 99%